Diversity, equity, and inclusion: Tackling under-representation and recognition of talents in geochemistry and cosmochemistry. (1st October 2021) - Pourret, Olivier; Anand, Pallavi; Arndt, Sandra; Bots, Pieter; Dosseto, Anthony; Li, Zimin; Marin Carbonne, Johanna; Middleton, Jennifer; Ngwenya, Bryne; Riches, Amy J.V.
Abstract: Diversity, at every step along the scientific path, drives innovative research. Scientific societies, like the Geochemical Society (GS) and the European Association of Geochemistry (EAG), have a significant influence over which discoveries and innovators are celebrated. Such choices impact the future of research, and therefore influence the evolution of our discipline and its relationship to the global community. Our professional societies are well positioned to define and promote the success of all scientists, including those from under-represented groups, through proactive advocacy, inclusive mentorship, awards, and leadership. At present, only binary gender data are available to examine the distribution of under-represented groups among memberships, awardees, and leadership positions. To assess gender diversity in the geochemistry and cosmochemistry community, we have reviewed available records of GS and EAG membership through Goldschmidt Conference attendees, and compared these to awardees and leadership data. Awards have in the past been disproportionately given to white men, though this is changing. The GS and EAG have taken positive steps to increase both diversity of awardees (e.g., broadened definition of Fellows criteria) and inclusion (e.g., mentoring efforts aimed at early career and underrepresented minority scientists). This work identifies strategies to continue to improve professional societies' recognition of excellent science resulting in a more diverse representation of awardees. The strategies (e.g., revisions to award criteria and procedures to enlarge and diversify nomination pools) will require ongoing analysis and modifications. Future work is needed to address historically under-represented groups. We must work together to create a legacy of inclusion.